Tombor maghi as an interfaith ritual: lived religion among Muslims and Christians in West Papua, Indonesia - Ngabalin, Marthinus; Lattu, Izak Y. M; Qurtuby, Sumanto Al; Tampake, Tony (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
This article explores the Tombor Maghi ritual among the Fakfak community in West Papua Province, Indonesia, which strengthens interfaith relations, particularly between Muslims and Christians. Originally part of a traditional marriage custom, the ritual has developed into a broader form of community solidarity involving cross-religious cooperation. While scholars in anthropology and sociology have extensively studied rituals, research that focuses explicitly on rituals within the context of inter-religious relations remains relatively underdeveloped. This study addresses three main research questions: how the Tombor Maghi ritual is practiced and interpreted by the Fakfak community across religious affiliations; what role the ritual plays in fostering interfaith cooperation and reinforcing communal solidarity; and what symbolic and social significance the ritual holds within the broader framework of lived religion and indigenous approaches to peacebuilding. This study employs a qualitative methodology, utilising a realist ethnographic approach. Data were collected through interviews and field observations conducted in Fakfak Regency. The findings indicate that Tombor Maghi continues to be preserved as a form of cultural dialogue that weaves together interfaith relations. The ritual reflects cultural knowledge that is created, transmitted, and practised in daily life. It provides a space for Muslims and Christians to collaborate through community-based initiatives, such as at mosques and churches. In light of these findings, further research related to this topic is suggested because there are still many interesting issues to discuss in connection with rituals that have become a philosophy in social life.